2010
DOI: 10.1007/s11033-010-0136-9
|View full text |Cite
|
Sign up to set email alerts
|

Induction of cytotoxicity by photoexcitation of TiO2 can prolong survival in glioma-bearing mice

Abstract: We have investigated the possibility that photoexcited titanium dioxide (TiO2) could inhibit the growth of malignant cells. We studied the anti-glioma effects of nano-TiO2 excited with ultraviolet A (UVA) irradiation both in vitro and in vivo. Transmission electron microscopy demonstrated that glioma cells take up TiO2 by phagocytosis, and vital staining revealed that TiO2 alone has no effect on glioma cell proliferation. However, if TiO2 was combined with UVA irradiation the proliferation rate was decreased s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(50 citation statements)
references
References 35 publications
0
50
0
Order By: Relevance
“…TiO 2 nanoparticles have many unique properties such as biocompatibility, chemical stability and optical properties [173]. It is because of these properties that there has been a recent increase in the use of TiO 2 nanoparticles in biomedical applications such as drug delivery [174][175][176][177][178][179], bioimaging [175], photoablation therapy [180][181][182][183][184][185] and biosensors [186,187], which will be discussed further in Section 4. Other metal oxide nanoparticles that are gaining interest in biomedical applications are cerium oxide (CeO 2 ) nanoparticles or nanoceria.…”
Section: Metal Oxide Nanoparticlesmentioning
confidence: 99%
See 3 more Smart Citations
“…TiO 2 nanoparticles have many unique properties such as biocompatibility, chemical stability and optical properties [173]. It is because of these properties that there has been a recent increase in the use of TiO 2 nanoparticles in biomedical applications such as drug delivery [174][175][176][177][178][179], bioimaging [175], photoablation therapy [180][181][182][183][184][185] and biosensors [186,187], which will be discussed further in Section 4. Other metal oxide nanoparticles that are gaining interest in biomedical applications are cerium oxide (CeO 2 ) nanoparticles or nanoceria.…”
Section: Metal Oxide Nanoparticlesmentioning
confidence: 99%
“…Further work is needed to optimise this photocatalytic cancer treatment as UVA irradiation can damage healthy cells [180]. The photoexcitation of TiO 2 nanoparticles was investigated to inhibit the growth of malignant glioma cells by Wang et al [181]. In vitro and in vivo studies were carried out using U87-MG brain cancer cell line and female BALB/c-nude mice which were injected with glioma cells and the TiO 2 suspension was injected under the skin.…”
Section: Tio 2 Nanoparticles As Nanocarriers In Targeted Drug Deliverymentioning
confidence: 99%
See 2 more Smart Citations
“…Similar results were found by Wang et al, who observed that the proliferation rate of U87 glioma cell line was decreased when TiO 2 nanoparticles were combined with UVA irradiation. Results from their work suggested that TiO 2 induction of glioma cell apoptosis is associated with changes in the expression of genes encoding Bcl-2 family members [317].…”
Section: In Vitro Toxicity Of Nanomaterialsmentioning
confidence: 99%